Recent Advancements in the Conversion-Type Pnictide-Based Electrodes for Li-Ion Batteries - Monconduit, L. (Journal of physical chemistry. C, 2014)
Nowadays conversion-type electrode materials definitively lie as the core of any research programs related to Li-ion batteries. Requirements are high capacity, good rate capability, and a long cycle life. Indeed, the goal of much lithium battery research is to achieve the highest energy density battery as possible. In the case of pnictide materials, such performances are the results of the following conversion reaction: M x X y + 2yLi ↔ xM0 + yLi3X (X = P, Sb; M = Fe, Ni, Co, ...). However, these materials are still suffering from serious issues such as (i) low Coulombic efficiency, (ii) high polarization, (iii) poor cycle life (volume expansion), and (iv) limited rate capability that unfortunately still prevent them for any close commercial viability. In this article, the most recent research developments of our group and through collaborations in this specific field will be reported. In the interest of overcoming the limitations listed above, a cautious and rigorous scrutinizing of the electrochemical behavior of any studied materials is necessary. In our research group, we have extensive experience in the use of sophisticated in and ex situ characterization tools, in the aim to probe bulk pnictide in the Li batteries and the electrolyte/electrode surface as well. Indeed, thanks to these methods, we could unambiguously show that electrochemical conversion reactions are leading to some unstable phases, which cannot be synthesized via common chemical reaction paths. One can observe the key role of the solid/solid Li3X/M0 interfaces in the reversibility of the conversion mechanism. Contrarily, during the process, the solid/liquid electrode/electrolyte interfaces are subject to continuous parasitic reactions which drastically limit the cycle life of the battery. Fortunately, both nanostructuration of the pnictide electrodes as well as the confinement of pnictide into a porous carbon matrix play a great role in improving the performance of the cell mainly due (i) to the shortening of the distance over which Li+ diffuses or (ii) to the buffer effect of the carbon matrix against the local volume change during the charge and discharge process.